INFLUENCE OF HATCHING EGGS STORAGE PERIOD UPON THE INCUBATION PARAMETERS IN JAPANESE QUAILS - Atanas GENCHEV (Journal of Central European Agriculture, 2009)
The purpose of the present study was to establish the effect of the prolonged storage of Japanese quail hatching eggs upon the incubation performance and the quality of hatched quail chicks. The duration of egg storage prior to their incubation had a weak negative effect on the weight loss from incubation day 0 to day 15. Eggs stored for 1-3 days exhibited a statistically signifi cantly higher weight loss than eggs stored for 8-11 days prior to incubation (P<0.001). Eggs stored for up to 8 days showed a tendency towards statistically signifi cant (P<0.05) longer period of incubation. The relationship between incubation period length and egg storage term was moderate, curvilinear and the effect of egg storage term was estimated at 14.3% оf the total dispersion of the trait. Despite the egg storage term prior to incubation, quails with high relative weight had a statistically signifi cant shorter period of incubation. The analysis of the combined effects of egg storage term and relative weight at hatching on incubation length showed that both factors complemented each other and even enhanced their effects upon the determination of the studied trait. The strength of these factors’ effects was estimated at 13.1% of the total dispersion of the incubation period length (P<0.001), with a leading role of the factor relative weight of hatched quail chicks.